(untitled) (Trabalho & Educação, 2017)
This article come from professional experience and research conducted, seeks to describe the relationship between work and imprisonment of women. The purpose of this reflection implies the need for critical reflection, historically and culturally, on the prison institution, women imprisoned in it and the issue of work and working relationships of these women before, during and after imprisonment. Therefore, it is important to emphasize the social role of women within this historical and cultural analysis, and specifically Latin American, considering the place that women occupied and occupy in the various social institutions. ___ Este artigo, oriundo de vivência profissional e pesquisas realizadas, busca descrever a relação entre trabalho e encarceramento de mulheres. A proposta desta discussão implica a necessidade de reflexão crítica, histórica e cultural sobre a instituição prisional, as mulheres nela encarceradas e a questão do trabalho e das relações de trabalho dessas mulheres antes, durante e após o cárcere. Assim sendo, é importante ressaltar o papel social das mulheres nesta análise histórica e cultural, e especificamente latino-americana, considerando o lugar que elas ocuparam e ocupam nas diversas instituições sociais.